Associated factors with negative self-perceived health in elderly assisted by primary care: ASSOCIATED FACTORS WITH NEGATIVE SELF-PERCEIVED HEALTH IN ELDERLY ASSISTED BY PRIMARY CARE (Revista Contexto & Saúde, 2022)
The aim of the present study was to verify the prevalence and factors associated with negative self-perceived health in the elderly assisted by primary care. An observational, cross-sectional analytical study was carried out with 241 elderly people from a community in Vitória, Espírito Santo. Self-perceived health was the outcome variable, and sociodemographic characteristics, lifestyle and health characteristics were the exposure variables. Data were analyzed using Pearson's Chi-Square test and the Prevalence Ratio was calculated for variables significantly associated with the outcome (p